Christian Oster's Picnic - Warren Motte (Studies in 20th & 21st Century Literature, 2002)
With eight novels published by the Editions de Minuit in the last decade, Christian Oster has established himself as one of the most interesting figures in a cohort of new French writers who are gradually redefining the novel as literary form…
Keywords: Christian Oster; new French writers; novel; literary form; conventional narrative; narrative; writer; reader; Le Pique-nique; fable; fiction